A279 THE EFFECT OF SHAM FEEDING ON SMALL BOWEL TRANSIT TIME IN PATIENTS UNDERGOING CAPSULE ENDOSCOPY. (1st March 2018) - Ou, G; Prichard, D; Galorport, C; Enns, R A
Abstract: Background: Small bowel capsule endoscopy (CE) has limited recording time and does not visualize the entire length of the small intestine in approximately 16.5% of the cases. We hypothesize that bacon-chewing is potent stimulus of cephalic response, which may reduce capsule transit times and improve complete examination rate (CER). Aims: To determine if sham feeding with bacon-chewing improves small bowel transit time and completion rate in patients undergoing capsule endoscopy. Methods: A prospective, single-blinded, randomized controlled trial at St. Paul's Hospital in Vancouver, BC has been recruiting since 01/2015. Inclusion: outpatient CE, age ≥ 19. Exclusion criteria: ongoing use of motility-enhancing or slowing drugs, active bowel obstruction, bowel resection, swallowing disorder, diabetes with end-organ damage, untreated thyroid disorder, and endoscopic placement of capsule camera. Given Imaging PillCam SB3 TM (Yoqneam, Israel) were used. Participants were assigned to either bacon or control group via concealed allocation based on unrestricted randomization sequence generated prior to study initiation. All subjects underwent bowel preparation with 2L PEG3350 with electrolytes the day before, and fasted ≥ 2h prior to the procedure. They were allowed to drink clear fluids and resume normal diet 2h and 4h post-capsule ingestion, respectively. Immediately after swallowing the capsule, subjects in the bacon group were asked to chew and spit 10 pieces of bacon, each over 30 seconds at one-minute intervals. This process was repeated an hour after ingesting the capsule. Gastric transit time (GTT), small bowel transit time (SBTT), and CER were compared between the groups. This study was approved by institutional research ethics board and registered on clinicaltrials.gov (NCT02353208). Results: Between 01/2015 to 09/2016, 109 CE's were included in the study, 89 of which were for GI bleeding. CE did not pass the pylorus in four patients in the bacon group during the recording, and were excluded from further transit time analyses. One and two additional CE's in the control and bacon group, respectively, did not reach cecum during recording and were excluded from SBTT analysis. There was no statistically significant difference in GTT, SBTT, or CER. Conclusions: Sham feeding by chewing and spitting bacon does not alter transit times or CER, and therefore should not be used in an attempt to improve CE yield. Funding Agencies: None